Cisco access control security : AAA administrative services - Carroll, Brandon (Networking technology series., 2004)
Hands-on techniques for enabling authentication, authorization, and accounting Understand the security concepts behind the AAA framework Learn message formats, communication, and message encryption using the TACACS+ and RADIUS protocols Configure and troubleshoot AAA on Cisco routers Understand where to position and install the CSACS in your network Explore and customize the CSACS interface Configure CSACS user accounts, user groups, and shared profile components Add AAA clients and manage network connections Configure external databases and perform database replication and backup Explore the various reports and logs available in CSACS Learn how AAA models apply to service provider environments Install and configure Cisco Access Registrar As network infrastructures evolve, it is increasingly important that access to vital corporate resources is vigilantly monitored and controlled. The Cisco identity management solutions, including Cisco Secure Access Control Server (CSACS), address this requirement, enabling security, control, and administration of the growing population of users that connect to corporate networks. CSACS, an essential component of the Cisco Identity Based Networking Services (IBNS) architecture, extends access security by combining authentication, user and administrator access, and policy control from a centralized identity-networking framework. This allows greater flexibility and mobility, increased security, and user productivity gains. Cisco Access Control Security provides you with the skills needed to configure authentication, authorization, and accounting (AAA) services on Cisco devices. Separated into three parts, this book presents hard-to-find configuration details of centralized identity networking solutions. Part I provides an overview of the AAA architecture, complete with discussions of configuring Cisco routers for AAA. Part II addresses enterprise AAA management with CSACS, including installation, configuration, and management details. Part III looks at service provider AAA management with Cisco Access Registrar. Full of detailed overviews, diagrams, and step-by-step instructions for enabling essential access control solutions, Cisco Access Control Security is a practical tool that can help enforce assigned access policies and simplify user management. "This book manages the rare combination of being highly accurate and technically astute, while maintaining an easy readability and flow. It is a great guide for s ...